Near field sound of a HRSG - Richarz, Werner (Canadian Acoustics, 2012)
The prediction of near field sound for large heat recovery steam generators (HRSG) is largely based on empirical data based on historical data. One of the reasons is that the underlying source mechanisms are rather complex. The unsteady pressure field inside the HRSG is a combination of turbulent and acoustic pressures. The methodology is based on a series of field measurements comprising both single microphone surveys and cross- spectral density/transfer functions measurements. It is common practice to assume that the near field sound pressure is determined by the local normal displacement of the panels. One approach, that has yielded good results, consists of subdividing the HRSG into a series of virtual ducts of varied cross-sections. The panel excitation consists of the local sound pressure, deduced from one dimensional duct acoustics, and a correction factor for the local boundary layer.